ARCHITECTURE CONCEPT OF ART DECO STUDY IN GRIFFITH OBSERVATORY, LOS ANGELES - Asa Aulia; Anisa Anisa (Ide dan Dialog Desain Indonesia (Idealog), 2020)
The development of art deco cannot be separated from the influence of the situation and conditions of the times, where at that time Europe was developing an industrial revolution, so that technological inventions developed rapidly. The modern architectural movement that was developing at that time also influenced the art deco style and gave it a modern touch. Modern at that time was defined as being more prominent than the surrounding environment. This art is manifested in the selection of striking colors, unusual proportions, new materials and decorations. Art deco expression increasingly gained a place in the world of art with the publication of the book Art Deco by Bevis Hillier in America in 1969. One of the buildings that experienced the euphoria of the art deco concept was the Griffith Observatory, which at that time was very different from the function of art deco buildings in general, which tended to be commercial and multi-storey. In examining the concept of art deco architecture at the observatory, the researcher will use the art deco principles by Bevis Hillier, namely: shaped, ornaments and materials. Researchers will analyze the Griffith observatory based on the part of these art deco elements. To analyze the exterior of the building, the method used is to collect adequate literature data from articles, journals and books related to the art deco building style and the Griffith observatory, then the data obtained were used as descriptive guidelines for the application of art deco at the Griffith Observatory. In addition, researchers also observed each shape and color combination of several images on the Griffith Observatory. The conclusion of this study is that the Griffith Observatory fully adapts the concept of art deco architecture to the classical ancient Greek building forms, the use of ornaments in the form of astronomical symbolization patterns on the main door, chevron patterns on the building walls, aztec leaf patterns on the dividing terrace of the upper floor and paintings of ancient Greek legends. in the interior and the use of limestone material with white and cream saturation which is commonly used in art deco concept buildings. Keywords : Art deco, Architecture Style, Griffith Observatory